2018
DOI: 10.1001/jamaoncol.2018.1908
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon Attitudes Toward the Omission of Axillary Dissection in Early Breast Cancer

Abstract: This study shows substantial variation in surgeon acceptance of more limited surgery for breast cancer, which is associated with higher breast cancer volume and multidisciplinary interactions, suggesting the potential for overtreatment of many patients and the need for education targeting lower-volume breast surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…High-volume breast surgeons were defined as those performing more than 50 breast operations annually within our integrated health delivery system. This definition has been used previously in a study by Morrow and colleagues, 23 and correlated with an increased adherence to evidence-based practice. Breast surgeons from all 21 medical centers in our health system meet quarterly to share best practices.…”
Section: Discussionmentioning
confidence: 99%
“…High-volume breast surgeons were defined as those performing more than 50 breast operations annually within our integrated health delivery system. This definition has been used previously in a study by Morrow and colleagues, 23 and correlated with an increased adherence to evidence-based practice. Breast surgeons from all 21 medical centers in our health system meet quarterly to share best practices.…”
Section: Discussionmentioning
confidence: 99%
“…ALN status is vitally important for therapeutic decision-making for early T stage TNBC patients in clinical [32]. Currently, sentinel lymph node biopsy and lymphadenectomy following pathologic diagnosis is the best approach for assessing ALN status of TNBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent report by Morrow on a survey that aimed to determine surgeon acceptance of Z0011 findings in the US showed that still 49% (175/357) of surgeons would definitively or probably recommend ALND for 1 SLN macrometastasis and 62.6% (221/353) would definitively or probably recommend ALND for 2 SLNs with macrometastasis. Lower propensity for ALND was significantly associated with surgeons who treated a higher volume of cases per year (21e50 cases: À0.19; 95% CI, À0.39 to 0.02; >51 cases: À0.48; 95% CI, À0.71 to À0.24; p < 0.001), surgeons who follow the recommendation of "no ink on tumor" as a negative margin (1e5 mm margin: À0.10; 95% CI, À0.43 to 0.22; no ink on tumor: À0.53; 95% CI,À0.82 to À0.24; p < 0.001), and surgeons with a higher proportion of cases discussed in a multidisciplinary tumor board (1%e9% of cases: À0.25; 95% CI, À0.55 to 0.05; >9% of cases: À0.37; 95% CI, À0.63 to À0.11; p ¼ 0.02), indicating the need for education targeted toward lower-volume breast surgeons [23].…”
Section: Change In Practicementioning
confidence: 99%